Effect of a combined Napier grass-oil palm frond feed on the in vivo and in sacco rumen fermentation and digestibility in goats - Leong, Zi Ping; Rajion, Mohamed Ali; Wong, Meng Joo; Ebrahimi, Mahdi; Goh, Yong Meng (2012)
In Malaysia, the lack of high-quality pasture remains the main factor slowing down the development of the ruminant livestock industry. The oil palm fronds (OPF), abundant and readily available agricultural by-products, appear as a promising solution, though they are unsuitable to be used as a sole feed. Therefore, this study evaluated a combined Napier grass (NP) and OPF (NP+OPF) feed by monitoring the digestibility, in vivo and in sacco, as well as the changes of rumen fermentation parameters (volatile fatty acids, rumen fluid pH and total protozoal counts). Fifteen two-year-old male rumen-fistulated Kacang crossbed goats were used and divided into three groups, where Treatment 1 group was fed 50% NP + 50% concentrate, Treatment 2 group 25% NP + 25% OPF + 50% concentrate, and Treatment 3 group 50% OPF + 50% concentrate. Following dietary adaptation of 10 days, the in vivo and in sacco digestibility and rumen fermentation parameters were determined. Compared to the 50% NP diet, the combined NP-OPF feed showed a significantly lower in sacco digestibility and total volatile fatty acid production (p< 0.05). However, it produced good in vivo digestibility, rumen pH and total protozoal counts which were comparable to the 50% NP diet and significantly better than the 50% oil palm frond feed. Thus, it is concluded that the combined NP-OPF diet is suitable as a ruminant feed.